Legal Crime Investigation Cases of Oil And Gas Transportation (BBM) in Polres Purworejo - Khusen Martono; Gunarto Gunarto (Jurnal Daulat Hukum, 2018)
The development of motor vehicles in Indonesia, particularly the development of two-wheel motor vehicles makes the supply of fossil fuels is increasing. The high fuel makes the fuel supply to the higher regions of Pertamina. Pertamina fuel supply in this area through a gas station (Fuel Filling Station General). This gas station into a formal point or an agent authorized to distribute fuel Pertamina to society. Criminal act of transporting fuel oil / fuel are subject to review of some aspects of the law to obtain justice. During these criminal cases haulage fuel seek of formal legal aspects applicable law, but a criminal act can not be seen from one side, but from some vantage as regional aspects and the economic aspects. The principle of legal justice that offers solutions to the public should be considered, although there is a violation of rules that apply in this transport process. Legal clash between the needs of society with Section 53 letters b and d of Republic Act number 22 of 2001 on oil and gas must have an alternative way out of sync between a solution and the rule of law.Keywords: BBM; Criminal; Justice; Law.